2022
DOI: 10.3390/ijms23169193
|View full text |Cite
|
Sign up to set email alerts
|

Neurospecific Molecules Measured in Periphery in Humans: How Do They Correlate with the Brain Levels? A Systematic Review

Abstract: Human brain state is usually estimated by brain-specific substances in peripheral tissues, but, for most analytes, a concordance between their content in the brain and periphery is unclear. In this systematic review, we summarized the investigated correlations in humans. PubMed was searched up to June 2022. We included studies measuring the same endogenous neurospecific analytes in the central nervous system and periphery in the same subjects. Not eligible were studies of cerebrospinal fluid, with significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Serum BDNF levels were conducted in each of the included studies. However, the data included in the systematic review conducted by Tikhonova et al [27] suggest that plasma or serum levels do not correlate with brain BDNF levels. More studies including the measures in the central nervous system are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Serum BDNF levels were conducted in each of the included studies. However, the data included in the systematic review conducted by Tikhonova et al [27] suggest that plasma or serum levels do not correlate with brain BDNF levels. More studies including the measures in the central nervous system are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in vivo human studies are of particular value, although in vivo determination of analyte content in the human brain is a non-trivial and difficult task due to the limited availability of human brain tissue for research because of ethical standards and technical capabilities. Further progress in the field would be provided by the development of advanced in vivo metabolomic analyses, neuroimaging techniques, and blood assays for exosomes of brain origin, as well as the emergence of novel approaches [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the study of neurospecific molecules and the correspondence of their content between the brain and periphery is of great interest. However, quite a few studies have investigated the correlation for neurospecific molecules between the brain and periphery in humans [9]. For example, the study by Gadad et al (2021) revealed a positive correlation between the levels of IL-6 and GDNF in the brain (Brodmann area) and blood plasma [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations